Respon Tanaman Cabai Rawit (Capsicum frutescens L.) Terhadap Pemberian Mikoriza dan Pupuk P di Tanah Ultisol - Satibi, Muhammad; Ichwan, Budiyati (Jurnal Media Pertanian, 2025)
Ulitsol land is one of the marginal dry lands that is still widely available for development as agricultural land, but there are limiting factors in the form of high Al and Fe content which causes P to be fixed. Mycorrhiza is expected to be a biological agent that helps increase the availability of P for plants. This research aims to provide information regarding the response to the application of mycorrhiza and P fertilizer to cayenne pepper plants (Capsicum frutescens L.) in Ultisol fields. This research was carried out in Karak Village, Bathin III Ulu District, Bungo Regency, Jambi Province at an altitude of 35 meters above sea level (MDPL). This research used a Randomized Group Design (RAK) with two factors. The first factor is the mycorrhizal dose which consists of 2 levels, namely 0 g and 15 g per plant. The second factor is the P fertilizer dose which consists of 5 levels, namely 0%, 25%, 50%, 75% and 100% (percentage of the recommended dose). So that 10 treatment combinations were obtained, each treatment was repeated 3 times. The variables observed were plant height, number of branches, total leaf area, dry stover weight, fruit number, fruit weight, root infection and phosphorus uptake. The results of the study showed that mycorrhiza had a real influence on the observed variables